Storytelling in Jazz Work as Retrospective Collaboration. Issue 1 (16th January 2017) - OKIJI, FUMI
Abstract: Storytelling has proved to be a useful metaphor in jazz commentary and analysis. Within such literature it is invariably solos, portrayed as discrete cultural articles, that "tell a story" through their adherence to internal coherence and logic. This prized autonomy is modeled on that which we find in the modern European tradition. Pathbreaking studies by scholars such as Ingrid Monson, Paul Berliner, and Keith Sawyer have redressed this hegemony in highlighting the importance of collaborative work in jazz. This essay needs to be considered a contribution to this focus. Yet approaches that emphasize interaction among band members tend toward dialogical metaphors and analytical frameworks that marginalize forms of creative "collaboration" that can occur retrospectively between musicians and vocalists who may not have even met. Drawing from Walter Benjamin's essay "The Storyteller: Nikolai Leskov, " this essay argues that storytelling in jazz is an intergenerational, accumulative effort in which we see a story continue to unfold with each new telling. It shows that there is generative tension between a musician holding on to his or her distinctive characteristics and approach, and their commitment to sharing (in) the story. Storytelling in jazz involves musicians adding "transparent layers" to the tradition, contributing to musical material, and collaborating with others (both contemporary and temporally distant) in a manner in which personal distinction is actively maintained. Through a consideration of John Coltrane's ideas concerning the centrality of community to the practice, storytelling in jazz is shown to be of extramusical social significance also.